Dimensionless squared jerk: An objective differential to assess experienced and novice probe movement in obstetric ultrasound. (5th November 2020) - Dromey, Brian P; Ahmed, Shahanaz; Vasconcelos, Francisco; Mazomenos, Evangelos; Kunpalin, Yada; Ourselin, Sebastien; Deprest, Jan; David, Anna L; Stoyanov, Danail; Peebles, Donald M
Abstract: Objective: Widely accepted, validated and objective measures of ultrasound competency have not been established for clinical practice. Outcomes of training curricula are often based on arbitrary thresholds, such as the number of clinical cases completed. We aimed to define metrics against which competency could be measured. Method: We undertook a prospective, observational study of obstetric sonographers at a UK University Teaching Hospital. Participants were either experienced in fetal ultrasound ( n = 10, >200 ultrasound examinations) or novice operators ( n = 10, <25 ultrasound examinations). We recorded probe motion data during the performance of biometry on a commercially available mid‐trimester phantom. Results: We report that Dimensionless squared jerk, an assessment of deliberate hand movements, independent of movement duration, extent, spurious peaks and dimension differed significantly different between groups, 19.26 (SD 3.02) for experienced and 22.08 (SD 1.05, p = 0.01) for novice operators, respectively. Experienced operator performance, was associated with a shorter time to task completion of 176.46 s (SD 47.31) compared to 666.94 s (SD 490.36, p = 0.0004) for novice operators. Probe travel was also shorter for experienced operators 521.23 mm (SD 27.41) versus 2234.82 mm (SD 188.50, p = 0.007) when compared to novice operators. Conclusion: Our results represent progress toward an objective assessment of technical skill in obstetric ultrasound. Repeating this methodology in a clinical environment may develop insight into the generalisability of these findings into ultrasound education.